Biomasa y carbono almacenado en las especies comerciales de un bosque de terraza baja del distrito de Mazán, Loreto. 2021 - Flores García, Juan José (2021)
Biomass and carbon storage have been reviewed in commercial species of floodplain forests in the district of Mazan, Loreto, Peru. Forest consensus database has been calculated from the commercial species of the marked out area. One of the forest consensus contract with wood purposes. The results show a biomass of 20 558,85 kg/ha and 6 455 684,68 kg, where M. Coriacea has the most quantity of 5 249,00 kg/ha and 4 788 337,36 kg and less quantity than sample B. Rubescens with 30,16 kg/ha and 9469,62 kg. The carbon storage is 10,279 tC/ha and 3227,84 tC M. Coriacea has the greatest quantity (7,62 tC/ha and 2394,17 tC); while B. Rubescens represents the lowest quantity (0,01 tC/ha and 4,73 tC). The diametral species of 60 cm to 69 cm (2,45 tC/ha and 769,71 tC) and 70 cm to 79 cm (2,30 tC/ha and 722,54 tC) represent the greatest quantity of carbon storage and the diametral species of 10cm to 109 cm (0,42 tC/ha and 134,32 tC) and also 110 cm to 119 cm (0,19 tC/ha and 61,48 tC) represent the lowest.